Pengaruh Kualitas Pelayanan dan Kinerja Karyawan PT Gapura Angkasa terhadap Kepuasan Penumpang di Bandar Udara Adi Soemarmo (Solo) - Bernad Rampa; Awan Awan (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
. In relation to employee performance as an executor of airport service users, human resources are needed who have good work motivation, so that they can influence work results according to service quality standards. The problems that the author observed during the OJT, the author saw a lack of time discipline to employees, there were several employees who came to work not on time and did not focus on serving passengers. The purpose of this study was to determine the extent to which the quality of PT Gapura Angkasa's pasasi services and the level of employee performance on passenger satisfaction at Adi Soemarmo Airport. This study uses quantitative methods with data collection techniques obtained directly, namely questionnaires, observation, and documentation distributed to 100 passengers at Adi Soemarmo Solo Airport. The data were analyzed using SPSS 25 software with normality test, multicollinearity test, linearity test, heteroscedasticity test, multiple linear regression equation, T test, F test, and coefficient of determination. The results of the T test conducted by researchers show that the significant value of 0.00% <0.05, then Ha is accepted and Ho is rejected, meaning that the dependent variable Y (Passenger Satisfaction) carried out by the PT Gapura Angkasa unit at Adisoemarmo Solo Airport.